Contexto social e práticas alimentares em creches públicas : compreensões e olhares de professores e pais sobre obesidade e sobrepeso em crianças - Fechine, Álvaro Diógenes Leite (2011)
Obesity has become a serious public health problem in several countries, including Brazil, affecting children of all ages, social class and ethnicity. Consequently, nurseries have become an important element in preventing childhood excess weight and obesity. This study aimed to understand the perceptions of nursery professionals and the parents of children attending these facilities, for their views on the factors that may influence obesity and excess weight in children and the prevention methods used. The study was conducted from January to September 2010.The population consisted of parents of children aged 2-5 years and teachers who work in public nurseries, from urban and rural areas of the state of Ceara, using a qualitative approach. Focus groups with parents and teachers were held to collect the data, which was analyzed using discourse analysis. The study found that teachers use the most appropriate methods to evaluate children’s weight gain, while parents can identify excessive weight gain in children when there is an excess of fat on the abdomen and arms. However, both agree that obesity can cause both serious physical and emotional problems for children. Parents and teachers were unanimous in confirming that eating habits begin at home, together with family members, with the mother bearing the primary responsibility. It was observed that teachers presented themselves as strong allies in developing strategies for education on diet and encouraging healthy lifestyles, since these are closely linked to the educational process and teachers have the opportunity to interact with children during the learning process. The use of processed foods was reported by parents and teachers as a factor predisposing weight gain in children, thus contributing to the development of overweight and obesity. In addition, it was found that despite the provision of school meals, there are cases of processed foods and treats being sold at the door of daycare centers in rural areas. Both parents and teachers complained about the difficulty of access to these items, especially those in rural areas. Teachers participating in the study complained about the lack of enthusiasm and involvement of parents in the children’s educational process, as parent’s attention centers on feeding their children. One important finding in the study, was the role of school cooks in the prevention of childhood obesity, since they are closely linked to the production of the 10 food served in the nursery. Finally it can be concluded that that the study did not clarify all the problems that intertwine the issues surrounding childhood overweight and obesity in the current context, but it shows that there are several factors that may be contributing to the phenomenon of rising childhood obesity in our country. Thus, the nursery appears to be an excellent place for developing intervention programs to tackle the conditions and risk factors for childhood obesity.